Dynamic team leadership coaching: Contribution to a new concept - Pereira, A. B.; Passos, A. M.; Teixeira, M. L. (EURAM 2019 Conference, 2019)
Limited published research has examined team coaching function processes. Through an extensive systematic literature review, this article explores team coaching knowledge and proposes a new concept by adding the Dynamic Team Leadership meta-theory. The concept Dynamic Team Leadership Coaching will contribute to advancements in team coaching research and supports the clarification of the "how" team coaching is used in practice towards the development of team performance management strategies.